Contested social representations of a religious ritual in the Philippines text mining online discourses on the Traslación - Medriano, Jose III; Torio, Jose Abelardo (2022)
Access online through this link: https://www.plarideljournal.org/article/contested-social-representations-of-a-religious-ritual-in-the-philippines-text-mining-online-discourses-on-the-traslacion
Keywords: Black Nazarene; Religious processions; Collective representation; Social media